2017
DOI: 10.22330/heb/321/042-052
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Olfactory Recognition Between Mother and Child

Abstract: The ability of infants to recognize their mother is an important factor in the development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When children aged 3.5-5 years took an olfactory recognition test based on tshirts from their mother versus an unfamiliar woman, 18 of 26 chose the mother's t-shirt in greater than 60% of the trials, but only eight in a statistically significant manner [57]. In another study, 3-5-year-olds had to select their mother's tshirt among five others: only 6 of 19 succeeded [133]. A further test [134] assessed whether 6-15-year-old children could identify their mother's or father's t-shirt (relative to a t-shirt worn by a sex-matched unrelated participant).…”
Section: (B) Social Diversification and Olfactory Recognition Of Conspecificsmentioning
confidence: 98%
“…When children aged 3.5-5 years took an olfactory recognition test based on tshirts from their mother versus an unfamiliar woman, 18 of 26 chose the mother's t-shirt in greater than 60% of the trials, but only eight in a statistically significant manner [57]. In another study, 3-5-year-olds had to select their mother's tshirt among five others: only 6 of 19 succeeded [133]. A further test [134] assessed whether 6-15-year-old children could identify their mother's or father's t-shirt (relative to a t-shirt worn by a sex-matched unrelated participant).…”
Section: (B) Social Diversification and Olfactory Recognition Of Conspecificsmentioning
confidence: 98%
“…It is also important for humans, as a study [101] found that 90% of mothers who participated were able to identify their babies' clothes by smelling them. A more recent study [102] concluded that mothers could also identify toddlers from smelling their clothes, with the success of identification higher than chance rates. Their results also show that those women who were able to correctly identify their child were more successful in distinguishing between male and female odours [102].…”
Section: Olfaction and Reproduction In Primatesmentioning
confidence: 99%
“…In keeping with this focus on female competition, Fisher (2017) provides a theoretical review, and a call to arms for researchers to investigate the role of both competition and cooperation between mothers. There is also some interesting research presented by Eryaman and Roberts (2017) investigating the presence of mutual olfactory recognition between mothers and offspring, and a manuscript by Pollet and Little (2017) offering guidelines for the use of forced choice methodologies in Ethology and Evolutionary Psychology.…”
Section: But What Of the Science?mentioning
confidence: 99%